Postoperative Gabapentin's Effect on Opioid Consumption and Pain Control Following Sinonasal Surgery. (14th July 2022) - Yang, Hong‐Ho; Wu, Tara J.; Suh, Jeffrey D.; Wang, Marilene B.; Holliday, Michael A.; Beswick, Daniel M.; Zhang, Huan; Wells, Christine; McCormick, Justin; Maxim, Tom; Regev, Aviva; Chandy, Zachariah K.; et al.
Abstract : Objective: This study investigates the impact of postoperative gabapentin on opioid consumption and pain control following endoscopic sinus surgery (ESS) and/or septoplasty. Methods: Patients who underwent ESS and/or septoplasty at a single institution from 2021 to 2022 were enrolled. All patients received postoperative hydrocodone‐acetaminophen for pain control. Half of the patients were also prescribed gabapentin for the first postoperative day in addition to hydrocodone‐acetaminophen. Subjects completed the Revised American Pain Society Patient Outcome Questionnaire 24 h and 7 days after surgery. We conducted a multivariable regression analysis to assess opioid consumption and improvement in pain scores in the first week between gabapentin and non‐gabapentin groups. Results: A total of 102 subjects, 51 in each arm, were enrolled. The mean age was 52 years and 53% of participants were female. Controlling for important baseline demographic, clinical, and surgically related variables, the addition of postoperative gabapentin was associated with a 44% (9.5 mg from 21.6 mg) reduction in opioids consumed in the first postoperative week (B = −9.54, 95% C.I. = [−17.84, −1.24], p  = 0.025). In addition, patients in both arms exhibited similar improvement in pain severity and sleep interference in the first 7 days (B = −1.59, 95% C.I. = [−5.03, 1.84], p  = 0.36). Conclusion: To the best of our knowledge, this is the first study to investigate the impact of postoperative gabapentin on opioid consumption and pain control following ESS and/or septoplasty. Our analysis demonstrated that postoperative gabapentin effectively reduced opioid use during the first postoperative week without compromising pain control. Level of Evidence: 3 Laryngoscope, 133:1065–1072, 2023